Islamic Movement In Malaysia: History And Tradition - Ahmad Nabil Amir; Tasnim Abdul Rahman (Rabbanica: Journal of Revealed Knowledge)
The paper discusses the historical origins of Islamic movement in Malaysia since colonial era. This was developed from two underlying bases; the ideal of reform and Islamic vision that was meant to awaken national consciousness and revitalised aspiration of pan-Islamism envisioned under the formidable authority of the Ottoman Caliphate. It examined the impact of this awareness in inspiring the movement for reform and reassertion of Islamic spirit and unity following the rising tide of Islam in broad socio-political context. The essential role of Syed Syaikh al-Hadi, Dr. Burhanuddin al-Helmy, Ustaz Abu Bakar al-Baqir, and Syed Muhammad Naquib al-Attas has marked unprecedented influence in the meaningful struggle for religious and intellectual development. The movement brought forth critical values and ideals of Islam that espoused for progressive and rational spirit and reconstruction of ijtihad and dynamic activism, based on inclusive moral and ethical norms and standards. The qualitative methodology used in this study focuses on content analysis and library research.The data was gathered by primary and secondary sources of document analysis, and it was technically analyzed utilizing interpretative, descriptive, historical, and comparative methods. The finding shows that the movement has brought fundamental reform by introducing the principle values and ideals of Islam and its underlying doctrine of tawhid and unity and projecting the idea of Islamization. By taking into consideration the principle of maqasid syariah (the higher objective of Islamic law) and its application in every communal sector, it has brought about some influence in influencing the governmental policy and direction towards incorporating Islamic values and tradition in socio-political context and framework.